GRAMATIKAL AL-QUR`AN: MENJAWAB TUDUHAN KESALAHAN GRAMATIKAL DALAM AL-QUR`AN - Buhori Buhori (INSTITUT AGAMA ISLAM NEGERI PONTIANAK, 2020)
Al-Qur'an is a holy book that is mu'jiz in nature, not only in terms of its content but also in terms of the language's beauty and its grammatical fluency. Al-Qur'an challenges those who still doubt it to write letters such as those in the al-Qur'an. Since the time of Prophet Muhammad PBUH. There is already a group that has envy and does not accept the holiness of the Qur'an. Nowadays, non-Muslims are again trying to find weaknesses and mistakes in the Qur'an. One of the errors they accuse is an error in the grammatical aspect of the Koran. This weakness will later be used as their argument, which states that the al-Qur'an is not a holy book that is ma'shum (protected from error). It is not a revelation but merely the creation of the prophet Muhammad. Therefore, in this paper, the author will answer the accusations of grammatical errors addressed in the holy book of the Koran. Keywords: grammatical, al-Qur`an, accusations, errors Al-Qur`an merupakan kitab suci yang bersifat mu`jiz, tidak hanya dari segi kandungannya, akan tetapi juga dari segi keindahan bahasa yang digunakan dan kefasihan tata bahasanya. Al-Qur`an memberikan tantangan kepada orang-orang yang masih meragukannya untuk membuat surat semisal yang ada dalam al-Qur`an.Sejak masa nabi Muhammad saw. sudah ada kelompok yang memiliki kedengkian dan tidak menerima atas kesucian al-Qur`an. Dewasa ini, kalangan non muslim kembali mencoba mencari kelemahan dan kesalahan dalam al-Qur`an. Salah satu kesalahan yang mereka tuduhkan adalah kesalahan dalam aspek gramatikal al-Qur`an. Kelemahan ini nantinya dijadikan sebagai argumentasi mereka yang menyatakan bahwa al-Qur`an bukanlah kitab suci yang ma`shum (terjaga dari kesalahan), ia bukan wahyu, namun semata hasil kreasi dari nabi Muhammad saw. Oleh sebab itu, dalam tulisan ini, penulis akan menjawab tuduhan-tuduhan kesalahan gramatikal yang dialamatkan pada kitab suci al-Qur`an. Kata Kunci: Gramatikal, al-Qur`an, Tuduhan, Kesalahan